Design of encoder and decoder module for optical code division multiple access (OCDMA) systems for zero cross correlation (ZCC) code based on arrayed waveguide gratings (AWGs) - Syed Mohamad Hamzah, Al-Junid; Sahbudin, Shaari; Syed Alwee Aljunid, Syed Junid; Anuar, Mat Safar (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org